Pendidikan Moral Menuju Harmonisasi Sosial - Davanosha Ayuta Putra; Edy Soesanto; Muhammad Dhani Al.F (Pusat Riset dan Inovasi Nasional, 2024)
Moral education in Indonesia is urgent, because in the last decade moral issues are still very complex. This emphasizes the importance of a holistic evaluation of Islamic education, which is based on divine and human values. This article also highlights changes in the curriculum for Islamic education and citizenship education, as well as the role of teachers in facilitating learning. The evaluation process is considered important in assessing the success of moral education, and this article suggests re-evaluating current evaluation methods to better measure the achievement of moral and ethical values. This article discusses the reconstruction of moral education evaluation towards social harmony. This emphasizes the importance of evaluating moral behavior that is rooted in the student's personality. This article argues that the current curriculum in Indonesia is not yet effective in achieving educational goals, and suggests that a reconstruction of evaluation methods is needed. This article proposes several strategies for evaluating moral education, including integrating moral education with real life situations, incorporating multicultural learning, and focusing on affective and psychomotor aspects of learning. The article concludes by highlighting the desired outcomes of moral education, such as tolerance, respect, and nationalism.